KLASIFIKASI USIA MENGGUNAKAN CIRI ORDE DUA - Mukti Qamal (TECHSI - Jurnal Teknik Informatika, 2013)
Identification of image is needed to facilitate the work of humans in terms of classification. The statistical method is one method often used to identify image. Identtification process in this research is a process where the images of children and adult face were used as an input for the purpose of age classification using the features of the second order. Calculated value is the value of Energy, Contrast, and Entropy. Calculation of statistical method of second order characteristics (Energy, Contrast and Entropy) is by measuring the contrast, granularity androughness of an area of the neighborhood relations between pixels in the image. System output is to determine the input image is the image of a child or adult. The test showed that percentage of the success was 83% for images those have been in practice, while the test for images outside the training showed the percentage success rate of 67%.